Synthesis of hollow trimetallic Ag/Au/Pd nanoparticles for reduction of 4-nitrophenol - Kwanjira Suwannarat (2018)
© 2017 Elsevier B.V. The hollow trimetallic Ag/Au/Pd nanoparticles with controllable Ag:Au:Pd ratio were successfully prepared by using a successive reduction method. Their optical properties, morphologies, structures, chemical compositions and electronic properties were carefully characterized by UV-vis, TEM, WDS, XRD and XPS techniques. The synthesized nanoparticles were also employed as catalysts for reduction of 4-nitrophenol. The results show that the trimetallic Ag/Au/Pd nanoparticles provided better catalytic activity than those obtained from bimetallic Ag/Au nanoparticles and monometallic counterparts. This study demonstrated that both atomic ratio of constituent metal and hollow interior structure strongly affect the catalytic activities of the synthesized Ag/Au/Pd nanocatalysts.